Mitochondrial Dynamics in the Drosophila Ovary Regulates Germ Stem Cell Number, Cell Fate, and Female Fertility - Garcez, Marcia; Branco-Santos, Joana; Gracio, Patricia C.; Homem, Catarina C. F. (Frontiers in Cell and Developmental Biology, 2021)
The fate and proliferative capacity of stem cells have been shown to strongly depend on their metabolic state. Mitochondria are the powerhouses of the cell being responsible for energy production via oxidative phosphorylation (OxPhos) as well as for several other metabolic pathways. Mitochondrial activity strongly depends on their structural organization, with their size and shape being regulated by mitochondrial fusion and fission, a process known as mitochondrial dynamics. However, the significance of mitochondrial dynamics in the regulation of stem cell metabolism and fate remains elusive. Here we characterize the role of mitochondria morphology in female germ stem cells (GSCs) and in their more differentiated lineage. Mitochondria are particularly important in the female GSC lineage. Not only do they provide these cells with their energy requirements to generate the oocyte but they are also the only mitochondria pool to be inherited by the offspring. We show that the undifferentiated GSCs predominantly have fissed mitochondria while more differentiated germ cells have more fused mitochondria. By reducing the levels of mitochondrial dynamics regulators, we show that both fused and fissed mitochondria are required for the maintenance of a stable GSC pool. Surprisingly, we found that disrupting mitochondrial dynamics in the germline also strongly affects nurse cells morphology, impairing egg chamber development and female fertility. Interestingly, reducing the levels of key enzymes in the Tricarboxylic Acid Cycle (TCA), known to cause OxPhos reduction, also affects GSC number. This defect in GSC self-renewal capacity indicates that at least basal levels of TCA/OxPhos are required in GSCs. Our findings show that mitochondrial dynamics is essential for female GSC maintenance and female fertility, and that mitochondria fusion and fission events are dynamically regulated during GSC differentiation, possibly to modulate their metabolic profile.